Perlakuan Akuntansi Pajak Pertambahan Nilai dan Pengaruhnya terhadap Laporan Keuangan dalam Program MBG di Kecamatan Babat - Luluk Dwi Mahbubah (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2025)
This study aims to analyze the application of Value Added Tax (VAT) accounting treatment and its impact on the quality of financial statements in the Free Nutritious Meal Program in Babat District. A qualitative descriptive approach was employed by conducting in-depth interviews, observations, and documentation analysis involving program managers, school representatives, and MSMEs as food suppliers. The findings reveal that VAT accounting treatment has not been fully implemented in accordance with existing regulations. Several transactions involving taxable entrepreneurs were recorded without separating the VAT component, causing the tax to be included as an operating expense instead of being recognized as input or output VAT. This condition affected the accuracy and fairness of the financial statements. However, there has been an improvement in understanding and implementation following socialization and assistance efforts. The study concludes that proper VAT accounting treatment plays a crucial role in enhancing transparency, accountability, and the reliability of financial reporting in government nutrition programs. Therefore, clear technical guidelines and continuous capacity building are necessary to improve financial governance in similar programs. Keywords: Value Added Tax, Accounting Treatment, Financial Statements, Free Nutritious Meal Program, Babat District.